1967
DOI: 10.1113/jphysiol.1967.sp008190
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro transfer of bovine immune lactoglobulin across the intestine of new‐born pigs

Abstract: 1. Everted sacs of pig intestine, used soon after birth, maintained transmural potentials and transferred water and glucose to the serosal surface. 2. Immune globulin, fed as bovine colostrum to the new‐born pig, appeared in the serosal fluid of everted sacs during incubation in bicarbonate saline. The particular segment showing maximum transferring ability varied between limits and appeared to depend on the amount or concentration of colostrum fed to the pig. Sacs from unfed pigs incubated in bovine colostrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

1968
1968
1999
1999

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…The presence of IgG in a great proportion of the sera of newborn pigs is in accordance with some reports (Pierce and Smith, 1967;Porter, 1969;Prokesova et al, 1969;Porter and Hill, 1970;Yabiki et al, 1974;Movsesijan et al, 1977;Chaniago et al, 1978) but contrasts with others (Lecce and Matrone, 1960;Kim et al, 1966a, b). The presence of IgG could possibly be explained by the development of immunocompetence by pig foetuses after about 70 days of gestation (Jousson, 197h;Metzger et al, 1978;Watson et al, 1979).…”
Section: -supporting
confidence: 89%
See 1 more Smart Citation
“…The presence of IgG in a great proportion of the sera of newborn pigs is in accordance with some reports (Pierce and Smith, 1967;Porter, 1969;Prokesova et al, 1969;Porter and Hill, 1970;Yabiki et al, 1974;Movsesijan et al, 1977;Chaniago et al, 1978) but contrasts with others (Lecce and Matrone, 1960;Kim et al, 1966a, b). The presence of IgG could possibly be explained by the development of immunocompetence by pig foetuses after about 70 days of gestation (Jousson, 197h;Metzger et al, 1978;Watson et al, 1979).…”
Section: -supporting
confidence: 89%
“…The mean IgG content of the colostrum of different sows, as also shown by others (Pierce and Smith, 1967;Jensen and Pedersen, 1979), showed marked variation.…”
Section: -supporting
confidence: 73%
“…It has been shown that the intestine of neonatal pigs absorbs homologous and heterologous proteins [3][4][5][6], other colostral proteins [7][8][9], and nonprotein macromolecules [10,11,13,15]. Kiriyama et al [14] reported that IgG, a small protein fraction and casein contained in colostrum were transported selectively into the systemic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal pigs absorb a wide variety of macromolecules such as homologous and heterologous proteins [3][4][5][6], other colostral proteins [7][8][9] and even nonprotein macromolecules [10][11][12][13] from the intestine to the blood for about the first 36 h of life. Kiriyama et al [3,14] reported that IgG in the colostrum is selectively absorbed through the intestinal lumen and transported into the systemic circulation via two routes, capillary vessels and lymph ducts in the neonatal pig.…”
Section: Introductionmentioning
confidence: 99%
“…Results obtained in this way differ in some important respects from others where the protein fed to animals has been recovered later from lymph or blood. Thus the apparent inability of the new-born pig intestine to distinguish between different proteins administered orally (Lecce, Matrone & Morgan, 1961;Pierce & Smith, 1967a) is not seen in vitro, the everted sac transporting albumin in marked preference to immune globulin (Pierce & Smith, 1966, 1967b. This demonstration of selectivity is interesting, but the many differences that exist between molecules of albumin and immune globulin, their size, shape and electrical charge at a physiological pH, limit what can usefully be said about the precise mechanism of transport.…”
Section: Introductionmentioning
confidence: 99%